Odpowiedzi

Najlepsza Odpowiedź!
2009-12-31T21:55:01+01:00
(x-√3)² - 2(x-√3)(x+√3) + (x+√3)² =
= x² - 2x√3 + 3 - 2(x² - 3) + x² + 2x√3 + 3 =
= x² - 2x√3 + 3 - 2x² + 6 + x² + 2x√3 + 3 = 12
  • Użytkownik Zadane
2009-12-31T21:55:13+01:00
(x-√3)²-2(x-√3)(x+√3)+(x+√3)²=x²-2√3x+3-2x²+6+x²+2√3x+3=12
2010-01-01T02:43:25+01:00
(x-√3)²-2(x-√3)(x+√3)+(x+√3)² =
= x² - 2x*√3 + (√3)² - 2[x² -(√3)²] + x² + 2x*√3 + (√3)²=
= x² - 2x*√3 + 3 - 2[x² - 3 ] + x² + 2x*√3 + 3
= x² - 2x*√3 + 3 - 2x² + 6 + x² + 2x*√3 + 3 =
= 12